Estudo de caso: uso da piezoeletricidade em pavimentos, mantendo suas características de geração de energia - Carvalho, Flávia Renata Prestes (Universidade do Vale do Rio dos Sinos, 2023)
Several highways in the country contain a large flow of vehicles. These, with their speed and weight, generate heat and friction on the pavements. Currently, this mechanical energy is wasted. With the aim of converting the vibration energy of vehicles into electrical energy, this work studies the incorporation of piezoelectric materials to make roads more energy efficient. Piezoelectricity is the effect of crystals that, when subjected to external pressure, deform their magnetic field, generating a potential difference that results in electric current. The purpose of this work was to analyze 20mm diameter piezoelectric tablets below the flexible pavement coating layer, through laboratory and field tests. In the laboratory, tests were carried out to evaluate the rigidity and performance of the system under loads of 10Kg, 50Kg, 150Kg, 250Kg and 350Kg, maintaining the characteristics of energy generation and aiming at the durability of the system during the succession of loads. In the field, the differences between the loads of passenger and SUV vehicles were evaluated, as well as the effect of speeds of 10Km/h, 20Km/h and 30Km/h, with the aim of maintaining the supply of energy microgeneration and allowing a considerable energy generation, even under adverse external conditions in which the material was applied. A positive contribution to the mechanical behavior in the laboratory and field was observed in relation to the effect of loads. Confirming previous studies, the greater the application of weights, the greater the effects of the electric current on the system. Thus, in the tests carried out, it was possible to validate the energy generation characteristics and the emissions generated were as expected. Therefore, this work proposes a renewable energy alternative in places with large movement of people and vehicles and the system is favorable for its integrity to be continued in future studies.
Keywords: Piezeletricidade; Microgeração de energia; Vibração de pavimentos; Eficiência energética; Captura de energia; Piezoelectricity; Energy microgeneration; Road vibration; Energy efficiency; Energy harvesting